2020
DOI: 10.1039/d0pp00133c
|View full text |Cite
|
Sign up to set email alerts
|

The bright side of sound: perspectives on the biomedical application of sonoluminescence

Abstract: Light is a physical phenomenon that is very important to human life, and has been investigated in its nature, behaviour and properties throughout human history although the most impressive improvements...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…Thereafter SDT cytotoxicity was evaluated confirming that SDT, i.e., 4T1 cells cultured with C-doped TiO 2 NPs and subjected to US exposure, induced higher cytotoxicity in 4T1 cells than the other treatment groups. Interesting was the speculation about the possible pathway of cell damage induced by SDT, where the authors suggested a role of sonoluminescence in the C-doped TiO 2 NPs activation to generate more ROS and kill 4T1 breast cancer cells [96]. Finally, in this work, to further investigate the cell death of 4T1 cells induced by SDT, an in vivo study was performed.…”
Section: Titanium Dioxide Npsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thereafter SDT cytotoxicity was evaluated confirming that SDT, i.e., 4T1 cells cultured with C-doped TiO 2 NPs and subjected to US exposure, induced higher cytotoxicity in 4T1 cells than the other treatment groups. Interesting was the speculation about the possible pathway of cell damage induced by SDT, where the authors suggested a role of sonoluminescence in the C-doped TiO 2 NPs activation to generate more ROS and kill 4T1 breast cancer cells [96]. Finally, in this work, to further investigate the cell death of 4T1 cells induced by SDT, an in vivo study was performed.…”
Section: Titanium Dioxide Npsmentioning
confidence: 99%
“…In this pioneering in vitro work, the role of targeted AuNps as sonosensitizers in SDT, an innovative anticancer approach where, it is generally accepted, a non-toxic molecule or system (chemical actuator), i.e., the sonosensitizer, is activated by US (physical activator), yielding oxidative damage by ROS generation, and consequent cancer cell death [94,95]. More specifically, the authors suggest that US, used at the frequency of 1.866 MHz for a total 5 min of exposure, through a physical phenomenon called sonoluminescence [96], might drive the AuNPs' plasmonic effect, as derived from LSPR, to be able to convert the photon energy to heat in order to induce cellular damage via ROS production. Analysis of intracellular ROS production was investigated in two different cell lines, HCT-116 and KB, and demonstrated that, while cells incubated with AuNPs in the absence of US and US alone did not encounter an increase in intracellular ROS productions, cells that were exposed to both AuNPs and US, i.e., sonodynamic treatment, were subjected to a significant increase in ROS production and therefore enhanced death rates.…”
Section: Gold Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…Porphyrins are well-known photosensitizers as their tetrapyrrole ring structure can be activated by light to generate ROS, causing damage to cell structures and cell death [33]. These features also make porphyrins also suitable sonosensitizers, i.e., compounds responsive to US, due to the hypothesis of the sonoluminescence occurrence under appropriate US exposure [34].…”
Section: Discussionmentioning
confidence: 99%
“…In sonodynamic therapy in which certain classes of drug can be activated by ultrasound, it has been suggested that MBSL light activates photosensitive drug [ 96 , 97 ]. Further studies are required on this topic.…”
Section: Applications Of Mbslmentioning
confidence: 99%